Fe3W3C/WC/Graphitic Carbon Ternary Nanojunction Hybrids for Dye‐Sensitized Solar Cells. Issue 4 (7th January 2015) - Liao, Yongping; Xie, Ying; Pan, Kai; Wang, Guofeng; Pan, Qingjiang; Zhou, Wei; Wang, Lei; Jiang, Baojiang; Fu, Honggang
Abstract Fe3W3C/WC/graphitic carbon (GC) ternary nanojunction hybrids are synthesized through a solid‐state pyrolysis process for dye‐sensitized solar cells (DSSCs). First‐principles calculations have been first employed to investigate the adsorption energy between I3− and Fe3W3C and WC nanoclusters. Scanning Kelvin probe images indicate that the work function changes greatly due to the formation of ternary nanojunctions, which favor fast photoelectron transfer. A photoelectrical conversion efficiency of 7.1 % is achieved based on Fe3W3C/WC/GC hybrid counter electrodes, which is much higher than those of pure GC (5.02 %) and WC/GC hybrids (6.11 %). It has been further revealed that Fe3W3C/WC/GC hybrid counter electrodes exhibit the best catalytic performances according to relevant electrochemical measurements, which can be attributed to fast photoelectron transfer due to the ternary junctions and the addition of Fe3W3C with more catalytic metallic atoms.